Specialized Television Media A study in redefining the concept - Challoob Jebur, Mohsin; Chasib Ajeelb, Alaa (Opción, 2019)
The growth of the specialized media today and its prosperity is a strong proof of the progress of society. When the society turns to the precise specialization among its members, it results in the expansion of scientific and cultural knowledge. The specialized media is a phenomenon of a historical and social nature. Its emergence and development is a complex and extended process that has taken place in history and society, Due to the importance of specialization and the public’s interest in specialized knowledge, the interest of media organizations in specialized subjects has become more and more important. It has become the majority of newspapers and radio and television programs, and most of them have led to the establishment of specialized newspapers and radio and television channels. The importance of this research from its attempt because of the scarcity of scientific studies that dealt with such topics, which will enhance the media library with new researches that accompany the phenomena of media accelerated change and emergence, as well as a distinct shift in the study of topics that represent the priority in the media, also represents a scientific view of an open window to know its aspects Different. This research aims at defining the specialized television media and describing its concept. And its structure, and this research is descriptive research. The researcher concluded that there are two absolute criteria for defining the concept of special- ized media: the content, the journalistic form and the two non-absolute relative criteria, namely, the public and the interest. It also concluded that the specialized television media is specific media content in the fields of politics, culture, econo- my, Sports or meeting and others presented in a press (media) or one of the forms of press (media) multiple as the specialized media on the corners of content,form and media in absolute and in addition to the corners of the audience and attention in relative, and developed a new classification of television channels Specialized: • Specialized satellite TV channels based on content. • Specialized TV channels based on format. • Specialized channels based on format and content. • Channels offering more than one content in multiple press for- mats. • Channels offer more than one press content.